Board of Directors and Financial Restatement: Evidence from The Two-Tier System - Ni Wayan Rustiarini; Ni Putu Shinta Dewi; Ni Made Sunarsih (Universitas Negeri Semarang, 2023)
Purpose : This study investigates the role of the characteristics of the Board of Directors (BoD) on financial restatements. The characteristics are reviewed based on board tenure, board size, board independence, female board, foreign board member, board level education, board accounting expertise, and dual board position. Method : The research sample is a manufacturing company on the Indonesia Stock Exchange for 2017-2021. The analytical tool used is logistic regression. Findings : This study found that five board characteristics negatively affect financial restatements: board tenure, board size, board independence, female board, and board accounting expertise. On the other hand, a dual position has a positive effect on financial restatements. Meanwhile, foreign board and board education do not significantly affect financial restatements. Novelty : First, considering BoD as a decision maker in the company, board characteristics influence group dynamics in collaboration and communication to implement corporate governance. Second, studies that analyze the impact of executive boards on financial statements still need to be expanded, especially in Indonesia, which adheres to a two-tier system. Third, previous studies that examine the role of BoD and financial restatements have provided contradictory evidence, and many studies still need to prove the effectiveness of the BoDs’ characteristics on financial restatements. Keywords : Director; Female; Restatement